2016
DOI: 10.1016/j.enpol.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Department of Defense energy policy and research: A framework to support strategy

Abstract: The Department of Defense (DOD) is the major consumer of energy within the Federal government, and it has been directed to implement cost cutting measures related to energy dependence through numerous Executive Orders and Congressional legislation. As a result, the DOD released an Energy Strategy which outlines ways to reduce energy requirements in order to meet both Presidential and Congressional mandates for energy security. With this research, we provide a historical review (1973-2014) of energy policy, leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Most existing literature generally does not discuss how to define sufficient energy availability to meet operational needs. Strakos et al discuss how DOD energy policy and research is organized into categories: energy research for reducing demand, expanding energy supplies, and building energy policy into the future force without a central mechanism to support strategic goals [64]. Hartranft focuses on US Army installation energy security, and recognizes that there is a diverse range of missions with scalable energy requirements [65].…”
Section: Related Researchmentioning
confidence: 99%
“…Most existing literature generally does not discuss how to define sufficient energy availability to meet operational needs. Strakos et al discuss how DOD energy policy and research is organized into categories: energy research for reducing demand, expanding energy supplies, and building energy policy into the future force without a central mechanism to support strategic goals [64]. Hartranft focuses on US Army installation energy security, and recognizes that there is a diverse range of missions with scalable energy requirements [65].…”
Section: Related Researchmentioning
confidence: 99%
“…3 b) which is interlinked with previous research on command and control, information users and etc. The articles present cases of managing strategic science and technology projects in the military (Shore, Zollo, 2014), solutions for strategy development (Mattila, 2016) and decisions for military operations using knowledge management (Strakos et al, 2016). Also, the articles analyze innovative approaches of knowledge management strategies, as ignorance management in multinational organizations (Israilidis et al, 2012) or usage of video-based performance support systems for online management information system (Ruffner et al, 2011).…”
Section: Fig1 Main Streams In Knowledge Management Research In Military: Inter-relationship Of Articlesmentioning
confidence: 99%
“…Therefore, the intensity and scope of military operations keep increasing, resulting in the consumption of all sorts of fossil fuel skyrocketed to great heights [1]. It has been reported that the United States Department of Defense (DOD) is the largest single energy consumer in the country [2]. In order to deliver petroleum products to forward operation and stationary bases, soldiers need to risk their lives in midway due to unexpected explosions caused by the enemy.…”
Section: Introductionmentioning
confidence: 99%